Unity 2021 Shaders and Effects Cookbook : Over 50 Recipes to Help You Transform Your Game into a Visually Stunning Masterpiece, 4th Edition. - Doran, John P. (Packt Publishing, Limited, 2021)
Implementing shaders in your games can be notoriously challenging due to the complex math that stands in the way of attaining realism in games. This fourth edition, updated to Unity 2021, covers everything you need to know about vectors, constructing lighting with them, and using textures to create sophisticated effects without the complex math.